EVALUASI STRATEGI GERAKAN SATU RUMAH SATU JUMANTIK DALAM PENCEGAHAN DAN PENGENDALIAN DEMAM BERDARAH DENGUE DI KOTA PEKANBARU - Adhisti Handarie Agung; Zahtamal Zahtamal; Zulkarnain Umar (Jurnal Ilmu Lingkungan, 2022)
The environment is one of the factors that influence the breeding and life of the mosquito vector Ae. aegypti. Environmental factors that can influence consist of the physical environment, the biological environment and the social environment. People's habits that are detrimental to health and lack of attention to environmental hygiene are social environmental factors that can affect the incidence of Dengue Hemorrhagic Fever (DHF). Policy for prevention and control of DHF in the form of prevention and control strategies for DHF according to the Ministry of Health of the Republic of Indonesia (2017) is the control of vector-borne dengue by prioritize community empowerment efforts and community participation through the one house one jumantik movement.This research is a qualitative research with a case study method that aims to evaluate the input, process and output of the one house one jumantik movement in the city of Pekanbaru. The study was conducted in Pekanbaru City with the interviewees consisting of staff from the Dengue Hemorrhagic Fever Eradication Section  of the Pekanbaru City Health Office, puskesmas officers, jumantik cadres and the community.The results showed that the implementation of the one house one jumantik movement in prevention and control of dengue fever in Pekanbaru City was still uneven due to lack of awareness and participation of human resources, especially policy makers and the community, the absence of written standard operating procedures, inaccurate reporting systems, limited infrastructure, no rewards and punishment, as well as limited funds and limited mobility due to the covid-19 pandemic. One of the things that supports the increase in ABJ is the availability of funds for the implementation of the one house one jumantik movement, especially the incentives for cadres who go down according to schedule so that cadres can actively carry out socialization, data collection and inspections to the community. The limited funds to support the one house one jumantik movement made this activity not run optimally. The activeness of cadres and the increase in ABJ are also in line with the decrease in dengue cases.